Dermatologic Manifestations in Patients with Metabolic Syndrome in Brazil (Global Journal of Human-Social Science, 2024)
Metabolic syndrome MS a cluster of cardiovascular risk factors associated with increased mortality exhibits systemic manifestations in various organs including the skin This study aimed to investigate the prevalence of dermatological manifestations in patients with MS attending primary healthcare units staffed by Family Health residents in Gurupi Tocantins Brazil This descriptive cross-sectional epidemiological study enrolled 93 men and women aged between the ages 25 and 60 y across four Basic Health Units and used a questionnaire administered during medical consultations In total 69 89 of samples exhibited dermatological manifestations Morbid obesity was the leading factor linked to MS and skin alterations with 100 of these patients presenting with some form of dermatosis the most identified cutaneous manifestations by prevalence were erythematous lesions papules and plaques vesicles and blisters scaling and changes in pigmentation The high prevalence of dermatological manifestations in patients with MS with pseudoacanthosis nigricans being the most frequent can alert healthcare professionals to suspect MS and prevent long-term complications
Keywords: cutaneous manifestations; family health; health services; primary health care